RELASI SYEKH NURUDDIN AR RANIRY DENGAN SULTAN ISKANDAR TSANI PADA ABAD KE-17 - Mastori Mastori; Zenal Arifin; Karmuji Abu Safar (Jurnal Pemikiran Islam, 2023)
This study discusses the relationship between ulama and umara' in the 17th century, namely sheikh Nuruddin Ar Raniry and Sultan Iskandar Tsani. This study was compiled using historical research methods with library sources in the form of books, research reports, articles and journals related to this research. The results of this study are: first, conceptually theologically, ulama and umara' are not separate. Ideally, umara has the characteristics of a clergyman. Second, the relation of ulama and umara' in the case of Sultan Iskandar Tsani and Syekh Nuruddin Ar Raniri is an integralistic-symbiotic relationship so that it has implications for strengthening da'wah and society.